KEDUDUKAN HUKUM PENYIDIK TERHADAP OBYEK PRAPERADILAN - Arief Dwi Atmoko (Fakultas Hukum Universitas Narotama, 2018)
The supreme court issued the principle of law number 4 in 2016 on prohibition of judicial decision for a review of pre judicial. Weighing of the award the constitutional court 21/PUU-XII/2014 IS the result a review article 77 KUHAP judicial, and the constitutional court number 65/PUU-IX/2011 is the result the state judicial to review the rate of article 83 verse 2 KUHAP. In shortcut number 4 years 2016 explained that phrase ‘ evidence ‘, beginning enough evidence is a minimum of two evidence any, as well as “the suspect”, “the seizure”, and “shake down”. Are including amongst the as an object pre judicial. As in the law and that there is no legal remedy again. Intended legal remedy was “for a review of the ban to the award pre judicial”. After shortcuts number 4 years 2016 former has been no longer legal remedy to a preliminary injuction, and now this pre judicial decisions really final.